Ultrasound Characteristics of the Hair Follicles and Tracts, Sebaceous Glands, Montgomery Glands, Apocrine Glands, and Arrector Pili Muscles. (20th December 2018) - Wortsman, Ximena; Carreño, Laura; Ferreira‐Wortsman, Camila; Poniachik, Rafael; Pizarro, Kharla; Morales, Claudia; Calderon, Perla; Castro, Ariel
Abstract : Objectives: To explore the capability of very high‐frequency ultrasound (US; 50–71 MHz) to detect the normal morphologic characteristics of the hair follicles and tracts, sebaceous glands, Montgomery glands, apocrine glands, and arrector pili muscles. Methods: A retrospective study, approved by the Institutional Review Board, evaluated the normal US morphologic characteristics of the hair and adnexal structures in a database of very high‐frequency US images extracted from the perilesional or contralateral healthy skin of 1117 consecutive patients who underwent US examinations for localized lesions of the skin and 10 healthy individuals from December 2017 to June 2018. These images were matched with their counterparts from the database of normal histologic images according to the corporal region. The Cohen concordance test and regional mean diameters of the hair follicles and adnexal structures were analyzed. Results: The normal hair follicles and tracts, sebaceous glands, Montgomery glands, apocrine glands, and arrector pili muscles were observed on US images and matched their histological counterparts in all the corporal regions. There was significant US concordance (κ = 0.82; P  = .0001) among observers. Regional mean diameters (millimeters) of the hair follicles, sebaceous glands, and apocrine glands are provided. Conclusions: The hair follicles and tracts, sebaceous glands, Montgomery glands, apocrine glands, and arrector pili muscles are detectable with very high‐frequency US, including some regional and anatomic variants. Knowledge of their normal US appearances is a requisite for detecting subclinical changes, understanding the physiopathologic characteristics, and supporting the early diagnosis and management of common dermatologic diseases.